The Oxidosqualene Cyclase from the Oomycete Saprolegnia parasitica Synthesizes Lanosterol as a Single Product - Dahlin, Paul; Srivastava, Vaibhav; Bulone, Vincent; McKee, Lauren S. (Frontiers in Microbiology, 2016)
The first committed step of sterol biosynthesis is the cyclisation of 2,3-oxidosqualene to form either lanosterol or cycloartenol. This is catalyzed by an oxidosqualene cyclase. Lanosterol and cycloartenol are subsequently converted into various sterols by a series of enzyme reactions. The specificity of the oxidosqualene cyclase therefore determines the final composition of the end sterols of an organism. Despite the functional importance of oxidosqualene cyclases, the determinants of their specificity are not well understood. In sterol-synthesizing oomycetes, recent bioinformatics and metabolite analysis suggest that lanosterol is produced. However, this catalytic activity has never been experimentally demonstrated. Here we show that the oxidosqualene cyclase of the oomycete Saprolegnia parasitica, a severe pathogen of salmonid fish, has an uncommon sequence in a conserved motif important for specificity. We present phylogenetic analysis revealing that this sequence is common to sterol-synthesizing oomycetes, as well as some plants, and hypothesize as to the evolutionary origin of some microbial sequences. We also demonstrate for the first time that a recombinant form of the oxidosqualene cyclase from S. parasitica produces lanosterol exclusively. Our data pave the way for a detailed structural characterization of the protein and the possible development of specific inhibitors of oomycete oxidosqualene cyclases for disease control in aquaculture.